1979
DOI: 10.1161/01.res.45.4.479
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of isolated canine coronary arteries to calcium ions after exposure to cholesterol.

Abstract: The abundance of membrane cholesterol is an important determinant of the functional properties of biomembranes. To determine whether arterial smooth muscle acquires altered contractile properties in a high cholesterol environment, isolated canine coronary arteries were exposed to cholesterol in stable aqueous solution. Cholesterol, 10(-12) to 10(-10) M, was an efficacious vasoconstrictor, as maximum contractions equaled those obtained with 15 mM KCl. Antiadrenergic interventions, including chemical sympathecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0
1

Year Published

1980
1980
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(32 citation statements)
references
References 31 publications
3
28
0
1
Order By: Relevance
“…Results demonstrate that isolated aortae from rabbits fed a high-cholesterol diet are supersensitive to the constrictor effects of ergonovine. This finding is in agreement with previous studies (12,13) indicating that changes in the lipid environment of vascular smooth muscle may alter arterial contractility.…”
Section: Introductionsupporting
confidence: 94%
“…Results demonstrate that isolated aortae from rabbits fed a high-cholesterol diet are supersensitive to the constrictor effects of ergonovine. This finding is in agreement with previous studies (12,13) indicating that changes in the lipid environment of vascular smooth muscle may alter arterial contractility.…”
Section: Introductionsupporting
confidence: 94%
“…17 Hypercholesterolemia, however, may be a significant factor in the diminished response to norepinephrine, since the vasoconstrictor response to norepinephrine was reduced in both the WHHL rabbit aortas and the hypercholesterolemic NZW rabbit aortas. Yokoyama and Henry 6 have previously shown that cholesterol added to the tissue baths augmented the responses of isolated arteries to the vasoconstrictor effects of CaCI 2 and KCI. The present study failed to demonstrate an increased response to KCI in aortic rings from WHHL rabbits compared with NZW rabbits.…”
Section: Discussionmentioning
confidence: 97%
“…Other investigators have suggested that hypercholesterotemia per se may augment the reactivity of blood vessels. 6 In the present investigation, we hypothesized that augmented vasoconstrictor responses occur in blood vessels obtained from hypercholesterolemic animals that are prone to devebp atherosclerosis.In these studies, we used the Watanabe heritable hyperiipidemic (WHHL) rabbit. 7 * Homozygous WHHL rabbtts produced by serial inbreeding have plasma cholesterol concentrations of 500 to 950 mg/dl, develop grossly visible aortic atherosclerosis by 5 months of age, 8 -1011 and have decreased numbers of functioning low density lipoprotein (LDL) receptors in several tissues.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Recently, Shimokawa and his colleagues reported that protein kinase C and Rho-kinase activity are augmented in coronary smooth muscle in animal models of coronary spasm (36). Thus, coronary spasm may also be caused by hypercontraction of coronary smooth muscle in response to an increase of intracellular calcium ions (41,42). Calcium antagonists, which can block the entry of calcium ions into the cell, are highly effective in suppressing coronary spasm (43).…”
Section: Coronary Spasm and Coronary Smooth Musclementioning
confidence: 99%